2002
DOI: 10.1016/s0960-9822(02)01111-9
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function for the Sm Proteins in Germ Granule Localization during C. elegans Embryogenesis

Abstract: General mRNA processing factors are traditionally thought to function only in the control of global gene expression. Here we show that the Sm proteins, core components of the splicesome, also regulate germ granules during early C. elegans development. Germ granules are large cytoplasmic particles that localize to germ cells and their precursors during embryogenesis of diverse organisms. In C. elegans, germ granules, called P granules, are segregated to the germline precursor cells during embryogenesis by asymm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 34 publications
6
54
0
Order By: Relevance
“…However, previous RNAi depletion of other splicing components did not disrupt P-granule patterns in embryos (Barbee et al 2002), suggesting that P-granule integrity and perinuclear localization in embryonic cells do not depend on pre-mRNA splicing. Our screen demonstrated that at least some pre-mRNA splicing factors are necessary for proper PGL-1 localization to granules at the nuclear periphery in embryos.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…However, previous RNAi depletion of other splicing components did not disrupt P-granule patterns in embryos (Barbee et al 2002), suggesting that P-granule integrity and perinuclear localization in embryonic cells do not depend on pre-mRNA splicing. Our screen demonstrated that at least some pre-mRNA splicing factors are necessary for proper PGL-1 localization to granules at the nuclear periphery in embryos.…”
Section: Resultsmentioning
confidence: 76%
“…Sm components of the splicesome have been shown to localize to germ plasm in multiple species, and previous RNAi depletion of the C. elegans Sm proteins disrupted P-granule patterns in embryos (Moussa et al 1994;Barbee et al 2002;Chuma et al 2003;Bilinski et al 2004;Barbee and Evans 2006). However, previous RNAi depletion of other splicing components did not disrupt P-granule patterns in embryos (Barbee et al 2002), suggesting that P-granule integrity and perinuclear localization in embryonic cells do not depend on pre-mRNA splicing.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The TACCchTOG-Aurora or TACC-chTOG-PCTAIRE complex(es) may serve several functions, including one during cell division. Another role might be in the establishment or maintenance of cell polarity (Richter, 2001); a role for Taxin-associated complexes in asymmetric cell division is also possible (Barbee et al, 2002;Berdnik and Knoblich, 2002); this might be one explanation of the hematopoietic stem cell defects in Tacc3 deficient mice (Piekorz et al, 2002). TACC1 might also participate in the regulation of cytokinesis and interact at the midbody with another molecular complex, including instead of Aurora A the midbodyassociated Aurora B kinase, or another mitotic kinase such as a Polo kinase.…”
Section: Potential Normal Function(s) Of Tacc1mentioning
confidence: 99%